Robot Force/Motion Tracking and Estimation of Contact Geometric Parameters - Karlsson,Filip (2025)
This thesis investigates the implementation and experimental evaluation of velocity controllers for force and motion control. It also explores how adaptive estimators and velocity control can be integrated cooperatively to improve the accuracy and efficiency of such control systems. Additionally, the thesis addresses how uncertainties affect position tracking performance, offering insights and solutions to mitigate their impact. These aspects are demonstrated through a series of experiments using a Universal Robots robotic arm, examining its ability to draw perfect circles on a sloped surface by employing hybrid force/motion control and adaptive estimators. The thesis also discusses theoretical foundations, limitations, insights, and safety considerations related to hybrid force/motion control tasks. The results demonstrated that the proposed hybrid force/motion controller was able to maintain stable contact forces and accurate trajectory following, even on inclined surfaces up to 10◦. This was made possible by integrating a normal plane estimator to adapt to surface variations. These results are crucial for developing reliable robotic systems that operate in unknown or dynamically changing environments, especially where cameras cannot be used. The proposed methods and findings have the potential to benefit a wide range of robotic applications that rely on similar control mechanisms, including tasks such as peg-in-hole insertion or surface interaction tasks like wiping.